Virtual real estate and innovative conflict resolution perspectives in the metaverse - López Rodríguez, Ana Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
With investments nearing 2 billion dollars in virtual real estate, there is growing competition among individuals and companies to be present in the metaverse. As individuals, businesses, and entities increasingly engage and invest in platforms such as Decentraland, The Sandbox, The Otherside, Axie Infinity, and Voxels, the concept of virtual property gains economic significance, reflecting the dynamics of traditional real estate markets. Considering that real-world conflicts tend to replicate in the metaverse, a variety of disputes related to virtual property and real rights over virtual real estate, as well as controversies arising from purchase or lease contracts of these assets, can be anticipated. However, there is no clear regulatory framework, and traditional conflict resolution methods do not seem aligned with the complexities presented by virtual environments. The latter is crucial to ensure legal certainty for investments. In this context, this article examines the adaptability of international private law regulations to the peculiarities of virtual real estate while exploring innovative dispute resolution mechanisms, such as Blockchain Dispute Resolution (BDR), which aims to play a significant role in the era of the metaverse.